Navigating Work-Life Balance: The Role of Personality, Burnout, and Technology in Indonesian Educators - Badaruddin, Badaruddin; Ibrahim, Ibrahim; Fatmasari, Fatmasari (UI Scholars Hub, 2025)
Research Aims: This study investigates the impact of personality traits, job demands, and emotional intelligence on work-life balance (WLB) among Indonesian educators, with burnout and boundary management styles serving as mediating factors. Design/Methodology/Approach: This study employed a quantitative research approach, gathering survey data from 295 Indonesian educators. Structural Equation Modelling (SEM) using SmartPLS 4 was conducted to examine direct, indirect, and moderating effects. Research Findings: Conscientiousness positively influences boundary management, while neuroticism has a detrimental effect. Increased job demands contribute to higher burnout levels, which, in turn, negatively impact both work-life balance (WLB) and boundary management. Burnout serves as a mediator in the relationships between job demands, conscientiousness, and neuroticism with WLB, whereas emotional intelligence moderates the impact of job demands on burnout. Theoretical Contribution/Originality: This study expands the Job Demands-Resources (JD-R) model and Boundary Theory by incorporating personality traits, burnout, boundary management, and emotional intelligence, providing a comprehensive framework for understanding work-life balance (WLB) in the education sector. Managerial Implication in the South East Asian Context: Educational institutions should prioritise strategies that enhance educators’ well-being. Measures such as optimised resource allocation, workload adjustments, and the promotion of boundary management practices can mitigate burnout and enhance job satisfaction. These interventions are particularly critical in Southeast Asian education systems, where resource constraints and high job demands pose significant challenges. Research Limitation & Implications: The cross-sectional design of this study restricts causal inferences, and the findings are specific to Indonesian educators, limiting their generalizability to other contexts.